1995
DOI: 10.1037/h0079673
|View full text |Cite
|
Sign up to set email alerts
|

Trauma contagion in partners of survivors of childhood sexual abuse.

Abstract: Partners of survivors of childhood sexual abuse may develop a "trauma contagion" marked by high levels of stress, doubts about to key personal values and assumptions about the world, and a tendency to be drawn into unconscious reenactments with the survivor of the abusive relationship. Various treatment interventions are discussed, especially conjoint work with the survivor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 22 publications
2
42
2
Order By: Relevance
“…It may require some time after brief conjoint therapy (4-12 months) for both partners to recognize and confirm basic changes in the quality of affective communication and in their capability to express emotions. Our findings were not closely consistent with those of Maltas and Shay (1995), who observed that when couples become involved in treatment services that are linked to a partner's sexual abuse history, they usually first focus on the sexual problems in their relationship. We found that conflict resolution and communication-skill development was the first priority so as to help ease emotional volatility in the relationship and to serve as a prelude to work on sensitive couple issues such as sexual expression and sexual satisfaction.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…It may require some time after brief conjoint therapy (4-12 months) for both partners to recognize and confirm basic changes in the quality of affective communication and in their capability to express emotions. Our findings were not closely consistent with those of Maltas and Shay (1995), who observed that when couples become involved in treatment services that are linked to a partner's sexual abuse history, they usually first focus on the sexual problems in their relationship. We found that conflict resolution and communication-skill development was the first priority so as to help ease emotional volatility in the relationship and to serve as a prelude to work on sensitive couple issues such as sexual expression and sexual satisfaction.…”
Section: Discussioncontrasting
confidence: 57%
“…In this respect, it can come as an unexpected difficulty to their partners (Maltas & Shay, 1995), who often find it difficult to provide comfort and support. Many partners seem to "provide additional opportunities for suffering" (Nadelson & Polansb, 1991, p. 482) rather than facilitating healing and recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects are considered "secondary," because they occur in those who have not been directly traumatized by the event. Frequently, these effects may resemble PTSD symptoms (Bramsen, van der Ploeg, & Twisk, 2002;Nelson & Wright, 1996), but may be less intense (Maltas & Shay, 1995).…”
Section: Secondary Traumatic Stressmentioning
confidence: 99%
“…These effects are considered "secondary" because they occur in those who have not been directly traumatized by the event. Frequently, these effects may resemble PTSD symptoms (Bramsen, van der Ploeg, & Twisk, 2002;Nelson & Wright, 1996), but may be less intense (Maltas & Shay, 1995).Several authors have described the secondary effects traumatic events have on children (Barnes, 1998;Steinberg, 1998), spouses and partners (Arzi et al, 2000;Bramsen et al, 2002;Lev-Wiesel & Amir, 2001;McCann & Pearlman, 1990;Nelson & Wampler, 2000;Nelson, Wangsgaard, Yorgason, Higgins Kessler, & Carter-Vassol, 2002;Nelson & Wright, 1996), therapists (Figley, 2002;McCann & Pearlman, 1990;Pearlman & Saakvitne, 1995), emergency and medical professionals (McCammon & Allison, 1995), direct and indirect witnesses (Weingarten, 2003(Weingarten, , 2004, and others who work and interact with trauma victims/survivors on a personal level. The dilemma with the secondary traumatization hypothesis is that there is limited empirical support for the theory.…”
mentioning
confidence: 99%